Adventures and Letters of Richard Harding Davis - Davis, Richard Harding, 1864-1916; Davis, Charles Belmont, 1866-1926 (Salt Lake City, UT : Project Gutenberg, 1996)
"Adventures and Letters of Richard Harding Davis" by Richard Harding Davis is a collection of autobiographical sketches and letters, likely crafted in the late 19th century. The narrative revolves around Davis's life, detailing his early experiences, education, and budding career as a journalist and author. The themes of familial influence, the impact of upbringing, and the exploration of identity in the face of societal expectations are prevalent in the early chapters, showcasing the author's formative experiences that shaped his literary career. At the start of this compilation, the reader is introduced to the author's childhood in Philadelphia, where he grew up in a nurturing yet demanding household. His early days are filled with camaraderie with his brother, and they often engaged in makeshift plays and adventurous explorations of their environment. As Richard transitions into his schooling years, he grapples with the pressures of academic performance while exhibiting a strong moral compass, often rallying against injustices in his academic environment. The opening chapters illustrate the interplay of Richard$1 (Bs early creative instincts and the support from his family, setting the stage for his future endeavors in writing and journalism. (This is an automatically generated summary.)s
Release date is 1996-01-01
Keywords: Davis, Richard Harding, 1864-1916; Authors, American -- 19th century -- Correspondence; Authors, American -- 19th century -- Biography; Foreign correspondents -- United States -- Biography; Davis, Richard Harding, 1864-1916 -- Correspondence